﻿SurRFE-Sub-rede de filtragens específicas - Galvão, Ricardo Kléber Martins (2006)
﻿The increasing of the number of attacks in the computer networks has been treated with the increment of the resources that are applied directly in the active routers equip-ments of these networks. In this context, the firewalls had been consolidated as essential elements in the input and output control process of packets in a network. With the advent of intrusion detectors systems (IDS), efforts have been done in the direction to incorporate packets filtering based in standards of traditional firewalls. This integration incorporates the IDS functions (as filtering based on signatures, until then a passive element) with the already existing functions in firewall. In opposite of the efficiency due this incorporation in the blockage of signature known attacks, the filtering in the application level provokes a natural retard in the analyzed packets, and it can reduce the machine performance to filter the others packets because of machine resources demand by this level of filtering. This work presents models of treatment for this problem based in the packets re-routing for analysis by a sub-network with specific filterings. The suggestion of implementa- tion of this model aims reducing the performance problem and opening a space for the consolidation of scenes where others not conventional filtering solutions (spam blockage, P2P traffic control/blockage, etc.) can be inserted in the filtering sub-network, without inplying in overload of the main firewall in a corporative network